Analysis of SERVQUAL Dimensions on Customer Satisfaction in Forming Customer Loyalty at Rainbow Gym, Semarang City - Adzim, Leon Islamey; Ikasari, Hertiana; Zakaria, Fakhmi; Damar, Haunan (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study analyzes the influence of the five SERVQUAL dimensions (tangible, reliability, responsiveness, assurance, and empathy) on customer satisfaction and its subsequent effect on customer loyalty at Rainbow Gym in Semarang, Indonesia. The research is motivated by a significant 37.65% decline in gym membership and negative customer feedback concerning interpersonal service quality. Methodology: A quantitative approach was employed using purposive sampling to gather data from 140 respondents. Data were collected via structured questionnaires and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) via SmartPLS 4. Results: The analysis shows that all five SERVQUAL dimensions have a positive and significant effect on customer satisfaction, with assurance and empathy being the most influential. Furthermore, customer satisfaction significantly drives loyalty. Findings: The study underscores the dominant role of interpersonal service quality especially assurance and empathy in enhancing satisfaction and fostering loyalty in a gym setting. Originality: This research uniquely explores the application of SERVQUAL in the fitness industry using a PLS-SEM approach, which is still rarely used in this context. Novelty: The study contributes new insights into how interpersonal service dimensions impact loyalty through satisfaction, specifically in the context of weight-training gyms in Indonesia. Conclusions: Rainbow Gym and similar businesses should prioritize enhancing interpersonal service quality through staff training and consistent service delivery to retain members and foster long-term loyalty. Type of Paper:Â  Quantitative research paper.